Between Stigma and Survival: The Role of Digital Backstage and Selective Disclosure in MSM Health Navigation in Palu, Indonesia - Fitri Sulistiyani; Nurdin Rahman; I Made Tangkas; Ahmad Sinala (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: In this study, we aimed to explore how Men Who Have Sex with Men (MSM) in post-disaster Palu, Indonesia, manage their sexual identities under religious conservatism, patriarchal norms, and heightened moral surveillance following the 2018 earthquake. Within this religiously conservative and disaster-affected context, our objective was to understand how MSM employ impression-management strategies to navigate visibility, stigma, and safety, and to analyze their implications for mental health, healthcare-seeking behavior, and overall well-being. This study addresses gaps in the literature by situating MSM experiences within Indonesia’s sociocultural and religious frameworks, thereby contributing to regional and cross-cultural analyses of LGBTQ+ identity negotiation in Southeast Asia. Methods: This qualitative phenomenological study employed in-depth interviews, photo-elicitation, and digital ethnographic observation over six months in Palu. A total of twenty-five MSM participants aged 18–40 were purposively recruited to ensure diversity of experience and social background. Sampling continued until thematic saturation was reached, meaning no new themes emerged during ongoing analysis. Data collection included semi-structured interviews and analysis of interactions on online platforms (e.g., Telegram, BlueD, and Instagram). Visual materials contributed to the coding framework by illustrating non-verbal expressions of impression management, later integrated into thematic synthesis. Ethical approval was obtained from the Institutional Review Board (IRB) of the Faculty of Public Health, Universitas Muhammadiyah Palu, following the British Psychological Society (BPS) and American Anthropological Association (AAA) ethical codes. Participants provided verbal and written informed consent, and all identifying details were anonymized. Results: The primary outcome of the study was an understanding of how MSM in Palu adaptively navigate identity, stigma, and safety through impression management. Key findings revealed that MSM maintain dual personas—performing heteronormativity in public (front-stage) while expressing their authentic identities within digital backstage spaces. Selective disclosure of sexual orientation was governed by contextual trust, relational safety, and fear of institutional stigma. Digital platforms functioned as crucial psychosocial and health-navigation spaces, enabling solidarity and access to information. However, overreliance on digital interactions sometimes intensified isolation and reproduced inequalities linked to digital literacy and class. While these adaptive strategies ensure survival under moral surveillance, they inadvertently reinforce structural stigma by normalizing concealment and restricting public visibility. Conclusion: In conclusion, this study contributes to understanding how Men Who Have Sex with Men (MSM) in Palu construct survival and well-being through impression management under conditions of religious-patriarchal stigma and disaster-induced moral tightening. It illustrates that dual personas, selective disclosure, and digital backstage practices function both as protection and as mechanisms that perpetuate invisibility. These findings inform the design of culturally sensitive, confidentiality-centered health interventions, emphasizing peer navigation, digital outreach, and faith-inclusive stigma reduction. Future studies should investigate the long-term mental health impacts of sustained concealment and digital dependency, advancing inclusive policies and provider training across Indonesia’s public health systems and the broader Southeast Asian region.